(untitled) (Perioperaciina Medicina, 2026)
In 2023, law enforcement agency launched a criminal case against the management and medical staff of a prominent regional medical centre due to significant discrepancies between the volume of medical services recorded in the Electronic Health System (EHS) and the actual medical care provided. The medical institution had entered into an agreement with the National Health Service of Ukraine (NHSU), under which payment for medical services was made on a global, per-patient basis. However, over a period of two years, medical workers systematically entered false information into the system, including data about services that were either never provided or provided in smaller amounts than what was required under the terms of the NHSU contract. Thе falsification resulted in inflated payments from the state budget. The case highlights the growing trend of criminal liability for falsifying medical data under the state medical guarantee program. The defendants are facing charges under two articles of the Criminal Code of Ukraine, with potential penalties including significant prison sentences. The case is currently under judicial review, with further investigations and witness testimonies expected. This case serves as a critical example of the consequences of such violations, both for the individuals involved and for the medical institution’s reputation.